Family Support Relationship with The Rate of Schizophrenia Patients in Puskesmas Rongkop District Gunungkidul Yogyakarta - Joko Subandono; Adi Heru Sutomo; Carla R. Marchira (Faculty of Medicine, Public Health, and Nursing, 2019)
Background: According to the result of Basic Health Research 2013 in Gunungkidul Regency, the prevalence of the serious mental disorders is 2.05 per mil, with the average in the Province of Yogyakarta of 2.70 per mil, where Gunungkidul Regency is categorized high. Visits of schizophrenics in the work area of Public Health Center/Pusat Kesehatan Masyarakat (Puskesmas) Rongkop rank to 8, and this shows the number of people with serious mental disorders is high. Most cases of mental disorders are found in the Petir Village, which is 37 people, spread in all hamlets. This public health concern needs family and community support so that the patients can re-socialize with their community.Objectives: This research was aimed to determine the relationship between family support and recurrence of schizophrenia, the level of family support for schizophrenia and the recurrence rate of schizophrenia in the work area of Puskesmas Rongkop Gunungkidul Yogyakarta.Methods: Population in this research includes families who have experienced schizophrenia in the work area of Puskesmas Rongkop located in Petir Village, Rongkop, Gunungkidul. The samples were taken by including 37 respondents of total sampling. The analysis of hypothesis testing of collected data was made by using the Spearmen Rho correlation test aided by SPSS 16.00 program.Results: Family support for patients with schizophrenia in the work area of Puskesmas Rongkop Gunungkidul Yogyakarta is 35.13% in the medium category. The recurrence rate of schizophrenia in the work area of Puskesmas Rongkop Gunungkidul Yogyakarta is 62.16% in the low category. There is a positive and significant correlation between family support and recurrence of schizophrenia in the work area of Puskesmas Rongkop Gunungkidul Yogyakarta with correlation coefficient 0.649 with 1% significance level.Conclusions: Family support for patients with schizophrenia in the work area of Puskesmas Rongkop Gunungkidul Yogyakarta is in the medium category. The recurrence rate of schizophrenia in the work area of Puskesmas Rongkop Gunungkidul Yogyakarta is in a low category. There is a positive and significant correlation between family support relationship with recurrence of schizophrenia in the work area of Puskesmas Rongkop Gunungkidul Yogyakarta.